Memorandum of understanding between Universiti Teknologi MARA and Isra University, Amman, Jordan / Fakulti Perakaunan - Universiti Teknologi MARA, Fakulti Perakaunan (Universiti Teknologi MARA (UiTM), 2020)
UiTM and Isra University will endeavour to strengthen, promote and develop cooperation on the basis of equality and mutual benefit.